Materials and Applications of 3D Printing Technology in Dentistry: An Overview - Min Jeong; Kyle Radomski; Diana Lopez; Jack T. Liu; Jason D. Lee; Sang J. Lee (MDPI AG, 2023)
Purpose. This narrative review aims to provide an overview of the mechanisms of 3D printing, the dental materials relevant to each mechanism, and the possible applications of these materials within different areas of dentistry. Methods. Subtopics within 3D printing technology in dentistry were identified and divided among five reviewers. Electronic searches of the Medline (PubMed) database were performed with the following search keywords: 3D printing, digital light processing, stereolithography, digital dentistry, dental materials, and a combination of the keywords. For this review, only studies or review papers investigating 3D printing technology for dental or medical applications were included. Due to the nature of this review, no formal evidence-based quality assessment was performed, and the search was limited to the English language without further restrictions. Results. A total of 64 articles were included. The significant applications, applied materials, limitations, and future directions of 3D printing technology were reviewed. Subtopics include the chronological evolution of 3D printing technology, the mechanisms of 3D printing technologies along with different printable materials with unique biomechanical properties, and the wide range of applications for 3D printing in dentistry. Conclusions: This review article gives an overview of the history and evolution of 3D printing technology, as well as its associated advantages and disadvantages. Current 3D printing technologies include stereolithography, digital light processing, fused deposition modeling, selective laser sintering/melting, photopolymer jetting, powder binder, and 3D laser bioprinting. The main categories of 3D printing materials are polymers, metals, and ceramics. Despite limitations in printing accuracy and quality, 3D printing technology is now able to offer us a wide variety of potential applications in different fields of dentistry, including prosthodontics, implantology, oral and maxillofacial, orthodontics, endodontics, and periodontics. Understanding the existing spectrum of 3D printing applications in dentistry will serve to further expand its use in the dental field. Three-dimensional printing technology has brought about a paradigm shift in the delivery of clinical care in medicine and dentistry. The clinical use of 3D printing has created versatile applications which streamline our digital workflow. Technological advancements have also paved the way for the integration of new dental materials into dentistry.